On the stress- and strain-based fatigue behavior of welded thick-walled nodular cast iron - Christoph Bleicher; Steffen Schoenborn; Heinz Kaufmann; Masoud Alizadeh-Sh (Fracture and Structural Integrity)
Nodular cast iron (GJS) represents one of the most widely used materials for vehicle, energy and heavy machinery industry. Nevertheless, foundries struggling with the influence of local material defects in GJS like pores, shrinkages and dross often leading to a locally reduced fatigue strength of the entire component. One measure to tackle those negative effects is the welding of the affected areas. This measure is then successful when locally achieved material strengths and surface qualities are higher than the component with the casting defect. Unfortunately, data for the lifetime and fatigue assessment of welded GJS are not present right now.